PENGARUH PEMBERIAN INFORMASI TERHADAP PENGETAHUAN DAN SIKAP CALON PENGANTIN DALAM UPAYA PENCEGAHAN STUNTING DI PUSKESMAS SEI JANG - Anjani Nurhasanah; Yunita, Prasida; Roza, Nova (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
ABSTRACT Stunting remains a major global public health concern that impedes human development. In Indonesia, the 2023 Indonesian Nutritional Status Survey (SSGI) reported a stunting prevalence of 19.6%. Early intervention during the preconception period is essential to ensure effective and sustainable outcomes. Prospective brides, particularly future mothers, play a critical role in stunting prevention by understanding its long-term impacts and adopting a balanced, nutritious diet to support optimal maternal and child health. This study aimed to evaluate the effect of information dissemination on the knowledge and attitudes of prospective brides regarding stunting prevention within the working area of Sei Jang Public Health Center, Tanjungpinang City. A quasi-experimental study design was employed, using a one-group pre-test and post-test approach. A total of 42 prospective brides participated and received health education through structured feedback sheets. A paired t-test was used to assess the impact of the intervention on knowledge and attitudes. The findings revealed a significant increase in both knowledge and attitude scores following the intervention. The mean knowledge score increased from 13.21 (pre-test) to 18.86 (post-test), while the mean attitude score rose from 27.48 to 42.07. Bivariate analysis indicated a statistically significant effect of the stunting education intervention on both variables (p-value = 0.000 < 0.05). Keywords : stunting prevention, health information, prospective brides